Overview of Microfinance and Economic Empowerment of Women: Evidence from Rural Microcredit Services in Ethiopia - Elias Berhanu (Journal of Women Entrepreneurship & Business Management (e-ISSN: 2583-8210), 2026)
The purpose of this article is to assess the impact of microfinance on women’s economic empowerment in a rural milieu in Ethiopia. Women significantly contribute to the household’s livelihood and the economy at large. However, they remain incessantly the poorest in the community. This is because of diverse reasons, including the scanty access to finance (credit) that represses their productive capacity. Microcredits change the livelihood of women, shifting them away from strenuous and environmentally destructive activities towards environment-friendly farm activities and small-scale businesses. A household survey was conducted using a questionnaire comprising a checklist of required items to describe and assess the role of microfinance in shaping the economic position of rural women. The study underscores that rural women enjoyed better participation in income-generating activities, increased savings and further access to multiple microfinance services after effective use of microcredit in the area. Despite various challenges, including arduous workload at the household level, resistance from family members and stretched social engagements in the community, women prove resilient, often backed by their family members. There is a noticeable shift in household dynamics as women’s contributions to household expenditure improve as a result of microcredit. Microcredit programs have led to real progresses in women’s economic and overall social empowerment in the rural community.